2022
DOI: 10.1177/03080226221135375
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of occupational therapy clinicians on the assessment and evaluation of adult handgrip strength

Abstract: Introduction: Handgrip strength (HGS) is commonly measured to assess hand function, however, little is known about how and why occupational therapists assess and interpret HGS. This study aimed to explore the experiences of occupational therapists who work with HGS. Additionally, the study explored what biological and functional factors occupational therapists believe influence adult HGS. Method: A qualitative study design utilising purposive sampling identified occupational therapy clinicians within Queenslan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Choice of lifestyle activities outside of employment was seen to influence HGS. This was supported by Myles et al (2022) who found HGS was influenced by hobbies, sport or unpaid work which requires increased physical demands. As hand function is required to perform most daily activities whether employment-related or during leisure time it is important to consider the influence on HGS of how an individual spends their time and the demands of the activities they are engaged with.…”
Section: The Influence Of Biological and Functional Factors On Hgsmentioning
confidence: 80%
See 4 more Smart Citations
“…Choice of lifestyle activities outside of employment was seen to influence HGS. This was supported by Myles et al (2022) who found HGS was influenced by hobbies, sport or unpaid work which requires increased physical demands. As hand function is required to perform most daily activities whether employment-related or during leisure time it is important to consider the influence on HGS of how an individual spends their time and the demands of the activities they are engaged with.…”
Section: The Influence Of Biological and Functional Factors On Hgsmentioning
confidence: 80%
“…Ethical approval (number) was granted by (anonymous) in August 2022. This research built on a previous study examining the experiences of occupational therapists within Queensland, Australia to include both occupational therapists and physiotherapists Australia-wide with the hope of allowing for improved transferability of the findings to clinicians who evaluate HGS more broadly (Myles et al, 2022).…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations